Synonyms of the New Testament - Trench, Richard C., (Richard Chenevix), 1807-1886. (Grand Rapids, MI : Wm. B. Eerdmans, 1880)
This volume, the standby of several generations of serious students of the new testament Greek, is the outgrowth of special lectures on the comparative value of words in the new Testament which the author delivered as Professor of Divinity at King's College, London. It is designed for the student who already has some working knowledge of the Greek language. As such it is an invaluable source of reference. In his "Profitable Bible Study" Dr Wilbur M. Smith states " Once one becomes accustomed to using this book he will find himself continually referring to it when desiring to distinguish accurately between the different shades of meaning of more or less similar New Testament Greek words."
This book has been published in many editions since it was first released at Cambridge in 1854.
Keywords: Bible. -- language, style; Biblical Greek -- textbooks